PENDIDIKAN PAUD BERBASIS MULTIKULTURAL - Arman Man Arfa (DIALEKTIKA, 2019)
ABSTRACT Early Childhood Education is a vehicle of education that is very fundamental in providing the basic framework for the formation and development of basic knowledge, attitude and skills in children. Given that Indonesia is a country with a diversity of cultures, multicultural education is the answer to many different backgrounds. Early-based early childhood education needs to be grown from an early age so that the future of society can be well ordered in accordance with the ideals of humanity in accordance with the culture of society. Multicultural education builds on existing cultural diversity, becoming a worldview that sees the world as the basis for the diversity of society and a part of life that bridges the various ethnic, religious and cultural life. Keywords: Education, Multicultural.